The effect of transcranial direct current stimulation on static and dynamic posture control in the elderly: a systematic review and meta-analysis - Wei, Yaru; Chen, Peng; Zhan, Jianglong; Yin, Lulu; Yu, Zhongqi; Wang, Lin (Frontiers in Aging Neuroscience, 2025)
PurposeThis systematic review and meta-analysis aimed to investigate the effects of transcranial direct current stimulation (tDCS) on static and dynamic postural control in older adults, with the goal of providing evidence-based support for tDCS interventions in fall prevention among the elderly.MethodsPubMed, Web of Science, Embase, Cochrane Library, Scopus and CNKI were searched from their inception to March 11, 2025, covering literature published in all languages. Eligible studies included randomized controlled trials or randomized crossover trials assessing the effects of tDCS on static or dynamic postural control in older adults. The methodological quality and risk of bias of included studies were assessed using the PEDro scale and the Cochrane Risk of Bias Tool, respectively. Meta-analysis was performed using Stata 14.0 with a random-effects model. Subgroup analyses and meta-regression were performed to explore potential moderators.ResultsA total of 19 studies were included in the systematic review, of which 14 were subjected to meta-analysis. Compared to control conditions, tDCS significantly improved following outcomes in older adults, static postural stability index (APSIstatic: p < 0.001; MLSIstatic: p < 0.001; OSIstatic: p < 0.001), single-leg stance time (p = 0.004), center of pressure (COP) sway area during quiet standing (p = 0.044), COP path length (p = 0.03), dynamic postural stability index (APSIdynamic: p < 0.001; MLSIdynamic: p < 0.001; OSIdynamic: p < 0.001), Timed Up and Go test (TUGT; p = 0.003), and stride time variability during walking (p < 0.001). Subgroup analyses indicated that tDCS efficacy varied according to stimulation site and intervention duration. Meta-regression further revealed that the effect of tDCS on single-leg stance time was influenced by mean age.ConclusionThese findings suggested that tDCS can significantly improve static and dynamic postural control in older adults. However, due to the limited number of included studies and substantial heterogeneity observed in some analyses, the current conclusions require further validation through high-quality research. Based on the available evidence, it is recommended that future studies focus on the application of tDCS in fall-prevention interventions among older adults, in order to provide stronger evidence for its implementation in clinical practice.Systematic review registrationThis systematic review was registered in PROSPERO (International Prospective Register of Systematic Reviews) (Unique Identifier: [registration number: CRD420251031377]). The protocol is publicly available at: [https://www.crd.york.ac.uk/PROSPERO/].